2011
DOI: 10.1007/s10705-011-9448-y
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic nitrogen fixation by legumes in two Chinese grasslands estimated with the 15N dilution technique

Abstract: Symbiotic nitrogen (N) fixation by legumes was investigated using the 15 N dilution technique in two Chinese grasslands: one in the north-eastern Tibetan Plateau and the other in Inner Mongolia in China. A small amount (0.03 g N m -2 ) of 15 N labelled (NH 4 ) 2 SO 4 fertilizer was evenly distributed in two soils. One month after the 15 N addition, four legumes (Astragalus sp., Gueldenstaedtia diversifolia, Oxytropis ochrocephala and Trigonella ruthenica) in the alpine meadow and two legumes (Thermopsis lanceo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 23 publications
(22 reference statements)
3
46
2
Order By: Relevance
“…We found that the %Ndfa of C. microphylla was about 90%, falling within estimated ranges (85-92) by previous observations in similar temperate grasslands (Yang et al, 2011). Given the %Ndfa reflects the proportion of N derived from the atmosphere through biological N fixation by legumes (Vallis et al, 1967;Temperton et al, 2007;Carlsson et al, 2009), our estimate indicate that the shrub legume mainly relies on its symbiotic fixation of atmospheric N. The choice of reference plants could influence the estimate accuracy of %Ndfa (Rennie et al, 1982;Holdensen et al, 2007), but a recent study proved the reference plants growing together with legumes can provide a more relatively reliable quantification of N 2 -fixation (Carlsson and Huss-Danell, 2014).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…We found that the %Ndfa of C. microphylla was about 90%, falling within estimated ranges (85-92) by previous observations in similar temperate grasslands (Yang et al, 2011). Given the %Ndfa reflects the proportion of N derived from the atmosphere through biological N fixation by legumes (Vallis et al, 1967;Temperton et al, 2007;Carlsson et al, 2009), our estimate indicate that the shrub legume mainly relies on its symbiotic fixation of atmospheric N. The choice of reference plants could influence the estimate accuracy of %Ndfa (Rennie et al, 1982;Holdensen et al, 2007), but a recent study proved the reference plants growing together with legumes can provide a more relatively reliable quantification of N 2 -fixation (Carlsson and Huss-Danell, 2014).…”
supporting
confidence: 88%
“…with mycorrhizal symbiotic systems). We inferred that the N fixed by C. microphylla in our studied temperate grassland would account for 75% of the gap of N demand and supply with the same method used by Yang et al (2011). This indicated that biological N 2 -fixation of C. microphylla plays a more important role in N dynamics in N-limited grasslands.…”
Section: à2mentioning
confidence: 65%
See 1 more Smart Citation
“…This indicates that legumes strongly but not completely rely on N 2 fixation in alpine meadows. Direct estimation of biological N 2 fixation by legumes at the same site using the 15 N dilution approach showed that biological N 2 fixation represented approximately 40% of N assimilation in M. ruthenica and G. diversifolia, and 81% in O. ochrocephala (Yang et al, 2011). The strong but incomplete reliance on N 2 fixation might be associated with low temperatures, which are far below the optimum of 20-35°C for nitrogenase (Dart and Day, 1971).…”
Section: Nutrient Limitation At the Plant Species Levelmentioning
confidence: 98%
“…However, their above-ground biomass was markedly reduced by the maximal N addition (Table 3). The legumes are adapted to low N conditions because they fix atmospheric N 2 via symbiotic rhizobia (Yang et al, 2011). However, they lose their advantage and are gradually outcompeted by grasses at high N level.…”
Section: Nutrient Limitation At the Plant Functional Group Levelmentioning
confidence: 99%